2006
DOI: 10.5194/angeo-24-2375-2006
|View full text |Cite
|
Sign up to set email alerts
|

A first comparison of irregularity and ion drift velocity measurements in the E-region

Abstract: Abstract. E-region irregularity velocity measurements at large flow angles with the STARE Finland coherent VHF radar are considered in context of the ion and electron velocity data provided by the EISCAT tristatic radar system, CUTLASS Finland coherent HF radar, and IMAGE fluxgate magnetometers. The data have been collected during a special experiment on 27 March 2004 during which EISCAT was scanning between several E-and one F-region altitudes along the magnetic field line. Within the E-region, the EISCAT mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…The points at large α , on the other hand, are consistently below (above) the cosine trend at small (large) flow angles. In Figure 4d we also show the trend V N = sinθ/4 (dotted line) suggested by earlier studies by Milan et al [2004] and Makarevich et al [2006a] (see also our section 3.1). One can notice from Figure 4d that the data at the largest aspect angle α = 2.63° highlighted by the solid lines exhibit a general increase with the flow angle and appear to be consistent with this trend.…”
Section: Observationssupporting
confidence: 85%
See 1 more Smart Citation
“…The points at large α , on the other hand, are consistently below (above) the cosine trend at small (large) flow angles. In Figure 4d we also show the trend V N = sinθ/4 (dotted line) suggested by earlier studies by Milan et al [2004] and Makarevich et al [2006a] (see also our section 3.1). One can notice from Figure 4d that the data at the largest aspect angle α = 2.63° highlighted by the solid lines exhibit a general increase with the flow angle and appear to be consistent with this trend.…”
Section: Observationssupporting
confidence: 85%
“…Following earlier studies by Kohl et al [1992] at VHF, by Moorcroft [1996] at UHF, and by Uspensky et al [2001] at HF that suggested that the ion drift velocity contribution to the E region irregularity velocity should be considered, Makarevitch et al [2002] interpreted this observation as being consistent with the linear theory formula in the reference frame of neutrals at the largest flow angles, θ ≅ 90°, where V e 0 C ≅ 0 and phase velocity V ph ≅ V i 0 C is independent of α . More evidence on the importance of the ion motions at large flow angles has been presented at VHF [ Uspensky et al , 2003, 2004; Makarevich et al , 2006a], at HF [ Makarevitch et al , 2004] and at small flow angles and large aspect angles at HF [ Milan et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies reported in the literature, a number of ionospheric signatures of flux transfer events by flux reconnection have been detected in the F region, using for example the Super Dual Auroral Radar Network radars, including fast poleward moving ions (500–2000 m s −1 ) and large turbulence [ Boudouridis et al ., ; Cerisier et al ., , and references therein]. Also, in the E region (110–115 km height) fast‐moving irregularities have been seen using both HF, VHF, and UHF radars [e.g., Makarevich et al ., ]. These are not completely understood but are considered to be the result of plasma‐instabilities (primarily the Farley‐Buneman instability) driven by strong magnetospheric electric fields when the E × B drift speed up to 2000 m s −1 exceeds the ion‐acoustic speed (~300 m s −1 ) [e.g., Gorin et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…In these calculations we used the typical values of collision frequencies obtained using the expressions given by Schunk and Nagy [1980] and the neutral densities taken from the MSISE‐90 (Mass Spectrometer Incoherent Scatter Extended) model [ Hedin , 1991]. Since the SuperDARN radars used were located in various parts of the world and since a data set spanning 3 years was employed in this study, the MSISE‐90 model was run for the time of 1 January 2004, 1630 UT and for the location of 69.0°N, 19.1°E (used by Makarevich et al [2006a]). The resulting values were v i = 726 s −1 and v e = 31243 s −1 .…”
Section: Modeling Of Flow and Aspect Angle Conditionsmentioning
confidence: 99%